STROKOG (stroke and cognition consortium): An international consortium to examine the epidemiology, diagnosis, and treatment of neurocognitive disorders in relation to cerebrovascular disease. Issue 1 (18th November 2016) - Sachdev, Perminder S.; Lo, Jessica W.; Crawford, John D.; Mellon, Lisa; Hickey, Anne; Williams, David; Bordet, Régis; Mendyk, Anne‐Marie; Gelé, Patrick; Deplanque, Dominique; Bae, Hee‐Joon; Lim, Jae‐Sung; et al.
Abstract: Introduction: The Stroke and Cognition consortium (STROKOG) aims to facilitate a better understanding of the determinants of vascular contributions to cognitive disorders and help improve the diagnosis and treatment of vascular cognitive disorders (VCD). Methods: Longitudinal studies with ≥75 participants who had suffered or were at risk of stroke or TIA and which evaluated cognitive function were invited to join STROKOG. The consortium will facilitate projects investigating rates and patterns of cognitive decline, risk factors for VCD, and biomarkers of vascular dementia. Results: Currently, STROKOG includes 25 (21 published) studies, with 12, 092 participants from five continents. The duration of follow‐up ranges from 3 months to 21 years. Discussion: Although data harmonization will be a key challenge, STROKOG is in a unique position to reuse and combine international cohort data and fully explore patient level characteristics and outcomes. STROKOG could potentially transform our understanding of VCD and have a worldwide impact on promoting better vascular cognitive outcomes.